Status Hukum Khitan Perempuan (Perdebatan Pandangan Ulama dan Permenkes RI No.1636/MENKES/PER/XI/2010) - Aisyatul Azizah (Sunan Kalijaga State Islamic University & The Asia Foundation, 2020)
Khitan bagi laki-laki adalah wajib. Hal ini berbeda dengan khitan perempuan. Permasalahan ini menuai kontroversi baik terkait praktik dan status hukum. Polemik besar bergulir pasca Majelis Ulama Indonesia (MUI) berfatwa No. 9A tahun 2008. Legal himbauan ini mengatur pelarangan khitan terhadap perempuan. Pelarangan juga dimaklumatkan WHO (World Health Organitation), badan kesehatan dunia ini mengungkapkan dampak negatif pada praktik khitan perempuan. Data 140 juta perempuan mengalami pendarahan, gangguan buang air kecil, kista, dan kemandulan akibat berkhitan. LSM kemudian memvonis khitan perempuan berbahaya. Larangan tanpa tegas pada khitan perempuan juga diterbitkan kementerian Kesehatan yang membatalkan Permenkes Nomor 1636/MENKES/PER/XI/2010 dengan Permenkes Nomor 6 Tahun 2014. Hal ini menjadikan aturan khitan perempuan kurang jelas dimasyarakat. Dalam status Hukum Positif dan agama,tidak ada pelarangan maupun penganjuran secara mutlak. Namun demikian, khitan perempuan merupakan tradisi yangdipercaya sebagai penyempurna agama dalamajaran pada prilaku kesopanan. Di Indonesia, khitan perempuan dirayakan khusus dan sebagai argumen pelestarian adat dan budaya.[Circumcision for men is mandatory in Islamic Syari’ah. It is different from female circumcision. The issue is reaping controversy both practice and legal status. Public polemics is one reason in the Indonesian Ulema Council (MUI) fatwa No. 9A of 2008. The law stipulates the prohibition of female circumcision. The prohibition is announced by the WHO (World Health Organization), the world health agency that reveals negative things in female circumcision. Data on 140 million women experienced bleeding, urination problems, cysts, and infertility due to circumcision. NGOs is the next convicted female circumcision as a dangerous practice. Health Ministry also published an unequivocal prohibition on female circumcision, which canceled the Ministry rule (Permenkes) No. 1636 / MENKES / PER / XI / 2010 with Permenkes No. 6/2014. It makes the concept of rules for female circumcision less clear in society. In the status of positive law and religion, there is no absolute prohibition or recommendation. However, female circumcision is a culture believed as a religious accomplishment to make polite women. In Indonesia, female circumcision is special celebrations and argument for the preservation of tradition and culture.]